Collected economic papers : volume 5 - Robinson, Joan. (Oxford : Basil Blackwell, 1979)
The first of these papers was the response to a request for a survey of the state of contemporary economic theory. The theoretical papers operate on two planes, an attempt to get the logic clear in a tightly specified model and an attempt to loosen it up in the form approximations to make it useful for discussion of actual problems.
Includes bibliographical references.
ne 18/10/2019
Loans
Keywords: Economics--Collected works